The challenge of developing drugs for neglected parasitic diseases - Mckerrow, James (Henry Stewart Talks, 2014)
The challenges of discovering and developing drugs for neglected tropical diseases, What is meant by a “neglected tropical disease”?, Identification of the organisms responsible for neglected tropical diseases, Alternative approaches to drug discovery including both target-based approach and phenotypic approach, Specific examples for drug leads or drug candidates discovered by these approaches, Repurposing of existing drugs for use against neglected tropical diseases.